Police Administration and Social Change in Thailand 4.0 Age - Bupta, Police Lieutenant Colonel Komsan; Yupas, Assoc. Prof. Dr. Yupaporn (Journal for Developing the Social and Community, 2017)
Thailand’s economy in the 4.0 era focusing on Sufficiency Economy Philosophy by using New-Innovations for improving system of the government and developing people’s potential into new world of challenging environments. The government sector has the important role in rules regulating and advocating for maximum efficiency. Therefore, the approach as the necessary principle to determine the development direction of police organization were; general administration, Law enforcement of officials operating level, personnel management and development, information technology using, performance with community.